Programming the internet of things : an introduction to building integrated, device-to-cloud IoT solutions - King, Andy (Andrew D.) (Beijing O'REILLY, 2021)
"Learn how to program the Internet of Things with this hands-on guide. By breaking down IoT programming complexities in step-by-step, building-block fashion, author and educator Andy King shows you how to design and build your own full-stack, end-to-end IoT solution--from device to cloud. This practical book walks you through tooling, development environment setup, solution design, and implementation"--Amazon.com
Part I : Getting started. Getting started -- Initial edge tier applications -- Part II : Connecting to the physical world. Data simulation -- Data emulation -- Data management -- Part III : Connecting to other things. MQTT integration: overview and Python client -- MQTT integration: Java client -- CoAP server implementation -- CoAP client integration -- Edge integration -- Part IV : Connecting to the cloud. Integrating with various cloud services -- Taming the IoT -- Appendix: Design road maps.
Includes bibliographical references (pages 371-374) and index.
Keywords: Internet of things -- Guidebooks; Cloud computing -- Guidebooks; Computer programming -- Guidebooks; Internet des objets -- Guides; Infonuagique -- Guides; Programmation (Informatique) -- Guides; Internet of things; Handbooks and manuals